2(3x+5)=10(x-1)-4x

Simple and best practice solution for 2(3x+5)=10(x-1)-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x+5)=10(x-1)-4x equation:



2(3x+5)=10(x-1)-4x
We move all terms to the left:
2(3x+5)-(10(x-1)-4x)=0
We multiply parentheses
6x-(10(x-1)-4x)+10=0
We calculate terms in parentheses: -(10(x-1)-4x), so:
10(x-1)-4x
We add all the numbers together, and all the variables
-4x+10(x-1)
We multiply parentheses
-4x+10x-10
We add all the numbers together, and all the variables
6x-10
Back to the equation:
-(6x-10)
We get rid of parentheses
6x-6x+10+10=0
We add all the numbers together, and all the variables
20!=0
There is no solution for this equation

See similar equations:

| -8(-8+a)=2(a+7) | | 20=-2(3x-1 | | 8+6=x-7 | | 2.5x+35x=100 | | -8(-6+3n)-3n=6(-4n+4) | | 15.9z-17.3=18.9z+19.6 | | 4-2n=8-n | | 3x-2=-28+3x | | 3/5(x+4/3)=1.041 | | 5x+6-10+3x=20-26 | | 100-35x=2.5 | | n/5-4=0 | | .25x=750 | | -16-11t=20-9t | | v-16=1 | | -8g=-5g-9 | | 9d-4d-d-9-3d=0 | | y/4*10=-14 | | 4x-3=-2x-2 | | –2k+6=–k | | -17=2u-5 | | 32=-4(y+-4) | | -4(6x-7)-8x=9x-300 | | t+3/8=7 | | 2(10+i)=20.5 | | 19=12+7(x-3) | | 3x+25=2x+40 | | x-4-3=-10 | | 4x-2+8-2x=10+12 | | -8.9s-11.97+0.75=18.87-7.2s | | x/5=1.33 | | 3x+19=3x-1 |

Equations solver categories